Leontodon ˣgrassiorum (Asteraceae, Cichorieae), a newly discovered hybrid between an Azorean and a mainland European taxon: Morphology, molecular characteristics, and phytochemistry. (June 2017) - Gemeinholzer, Birgit; Granica, Sebastian; Moura, Mónica; Teufel, Linda; Zidorn, Christian
Abstract: In Seefeld, Austria, Leontodon ˣ grassiorum Zidorn, a new Leontodon s.str. (Asteraceae, Cichorieae) hybrid was discovered. The new nothospecies is a hybrid between an Azorean endemic Leontodon species, commercially available as an ornamental plant, the recently described Leontodon hochstetteri M.Moura et L.Silva, and the most common Leontodon s.str. species in Austria, L. hispidus L. The origin of the new hybrid is discussed as well as the proper naming of its Azorean parent established. The new hybrid was morphologically and phytochemically characterised. Moreover, DNA-samples were analysed and discussed in the context of hybridization. The observed patterns are discussed with special emphasis on the importance of chemical markers in the discovery and characterisation of hybrids. Highlights: Leontodon ˣ grassiorum Zidorn, a new Leontodon s.str. hybrid was discovered. The new nothospecies is a hybrid between an Azorean and a mainland European taxon. Macromolecular, morphological and phytochemical characters are presented. Macromolecular data revealed Leontodon hochstetteri as the maternal parent. Phytochemical data identified Leontodon hispidus as the paternal parent.